2008
DOI: 10.1258/acb.2008.007252
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete laboratory request forms: the extent and impact on critical results at a tertiary hospital in South Africa

Abstract: Background: Research has demonstrated that most laboratory errors occur in the preanalytical phase of testing. In view of the paucity of studies examining preanalytical errors, we evaluated our laboratory request forms for the frequency and impact of incomplete data. Methods: This study examined all request forms received at our laboratory during a five-day period. The forms were scrutinized for the presence of specific parameters. The impact of abbreviated diagnoses was analysed, as well as how lack of ward o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
4
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 14 publications
6
65
4
4
Order By: Relevance
“…A similar study done by Nutt et al [10] reported that the information regarding the details of treating physician was missing in 61.2% the details of diagnosis was not indicated in 19.1% whereas in 80.9% where the diagnosis was mentioned, 37.3% were in the abbreviated forms. In total of 151 Critical results encountered in their study 19.9% were not communicated to physicians.…”
Section: Discussionmentioning
confidence: 70%
“…A similar study done by Nutt et al [10] reported that the information regarding the details of treating physician was missing in 61.2% the details of diagnosis was not indicated in 19.1% whereas in 80.9% where the diagnosis was mentioned, 37.3% were in the abbreviated forms. In total of 151 Critical results encountered in their study 19.9% were not communicated to physicians.…”
Section: Discussionmentioning
confidence: 70%
“…First, the multiple imputation methods used here are open to misclassification errors which may have skewed the distribution of ages, sex, or diagnoses. Similarly, because of incomplete and nonstandardized reporting by prescribing clinicians (a chronic problem reported elsewhere in Africa [54]), the imputation model could not include diagnoses that were not captured during the retrospective data collection process. This may have resulted in a loss of fidelity on the diversity of diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similar study done. 8 reported that the information regarding the details of treating physician was missing in 61.2% the details of diagnosis was not indicated in 19.1% whereas in 80.9% where the diagnosis was mentioned,37.3% were abbreviated forms. In total of 151 critical results encountered in their study 19.9% were not communicated to physicians.…”
Section: Discussionmentioning
confidence: 99%
“…74.3% (110) of the preanalytical errors were attributed to: request forms lacking address (40, 27.0%); test not done in biochemistry lab (24, 16.2%); specimen drawn in wrong tube (20, 13.5%); specimen without request forms (10, 6.8%); unlabeled specimen (8,5.4%); and inadequate/insufficient sample after centrifugation (8,5.4%). The remaining 25.7% (38) of the pre-analytical phase errors are associated to: no patient name or identification number (7, 4.7%); contaminated specimen bottle (6, 4.1%); mismatched information on request form and specimen container (5, 3.4%) this could be attributed as a result of manual registration as shown in Plate 1; no specimen received yet there is request form (5, 3.4%); specimen not paid for (5, 3.4%); leaking specimen/ broken container (3, 2.0%); wrong specimen (3, 2.0%); specimen clotted yet test requires unclotted specimen (2, 1.4%); test not well specified (1, 0.7%); and wrong test compared to the container type (1, 0.7%).…”
Section: Pre-analytical Phase Errorsmentioning
confidence: 99%